Clinical presentation patterns and neurological status among stroke subtypes - Rahman, M. Mizanur; Rahman, M. Habibur; Islam, Safikul; Islam, Mohammad Aminul; Khairuzzaman, M.; Zabin, Nisat; Hamid, M. Kawser (International Journal of Advances in Medicine, 2025)
Background: Differentiating stroke subtypes through distinct clinical presentation and neurological severity is essential for prompt management, especially in resource-constrained settings. This study aimed to compare clinical presentation patterns and neurological status among ischemic and hemorrhagic stroke patients in Bangladesh. Methods: A cross-sectional observational study was conducted among 100 adult stroke patients admitted to a tertiary hospital. Clinical features and neurological severity (Glasgow coma scale, GCS) were assessed and compared by stroke subtype. Predictors of impaired consciousness were identified using Cox regression analysis. Results: Among participants, ischemic stroke (74%) predominated over hemorrhagic stroke (26%). Hemorrhagic stroke was significantly associated with impaired consciousness (80.76% versus 59.45%; p=0.023), headache (80.76% versus 45.94%; p=0.004), vomiting (73.07% versus 41.89%; p=0.019), neck rigidity (80.76% versus 6.75%; p<0.001), hiccups (46.15% versus 22.97%; p=0.041), and convulsions (30.76% versus 12.16%; p=0.041). Unconsciousness (GCS≤8) was notably higher in hemorrhagic stroke (38.5% versus 20.3%; p=0.041). Cox regression identified hemorrhagic stroke (HR 2.85, p=0.006), neck rigidity (HR 3.41, p=0.003), convulsions (HR 2.12, p=0.047), age >55 years (HR 1.26, p=0.01), and BMI >30 (HR 1.08, p=0.03) as independent predictors of impaired consciousness. Conclusion: Significant subtype-specific clinical presentations and neurological impairment were observed, with hemorrhagic stroke associated with greater severity. Enhanced clinical awareness and targeted management strategies are essential in improving acute stroke care outcomes in Bangladesh.